Cultural adaptation of children's behavior questionnaire (CBQ) short form in a disadvantage community in Bangladesh - Akhter, Syeda Rezwana (BRAC University, 2010)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Science in Early Child Development, 2010.